Anaerobic capacity in soccer players from different competitive levels: Comparison of players in different field positions - Vanderson Luis Moro; Kenji Fuke; Lucas Cancian; Silvana Corrêa Matheus; Antonio Renato Pereira Moro (Motricidade, 2012)
The aim of this study was to compare anaerobic capacity in professional soccer players of different competitive levels in their respective positions in the game, early in the preseason. The study group consisted of 44 male athletes belonging to two groups (A and B) of different competitive levels. Group A was composed of 20 athletes participating in the Sagres League - Portuguese. Group B was composed of 24 athletes participating in the 2nd division Championship Gaucho - Brazil. For the assessment of anaerobic capacity it was applied the Running-based Anaerobic Sprint Test - RAST. For data analysis it was used the Student t test for independent samples and analysis of variance (ANOVA One Way) supplemented with post hoc Tukey. Results showed that group A athletes performed better on the average power and worst values for the fatigue index. In the group A it was found statistical difference between attacks and other two positions (midfielder and side back) for the fatigue index. It is concluded that there was significant differences in anaerobic capacity, measured at the start of the preseason, evaluated soccer players who work in competitions of different levels and positions play (group A).